Factors influencing acceptance or rejection regarding being the host community for post-disaster resettlements in developing countries. (1st February 2021) - Geekiyanage, Devindi; Keraminiyage, Kaushal; Fernando, Terrence; Jayawickrama, Thilini
Abstract: Post-disaster relocations have both positive and negative impacts on host communities. Receiving the host community's willingness to host the new community is essential to ensure integration and the sustainability of the new resettlement. This "willingness" is influenced by a variety of factors which have not been adequately studied by researchers and policymakers. This study, therefore, investigates the latent variables influencing a host community's decision to accept or reject disaster-induced resettlements. The study employed a survey approach utilising a questionnaire that contained 70 factors influencing host communities' perspectives on resettlements. A randomly selected 250 respondents from host communities were asked to indicate the factors that influence their level of agreement to be the host for displaced parties based on a 1–5 Likert-scale. The responses were analysed using the factor analysis: principal component analysis (PCA) and exploratory factor analysis (EFA) respectively. The PCA extracted 16 components which influence a host community's decision to accept/reject displaced communities (which account for nearly 70% of the total variance). The three most significant components were the impact on livelihoods and access to resources (total variance of 13%), political power and human wellbeing (9%), access to public services and social security (7%). The EFA revealed 58 sub-latent variables consisting of a majority of rejection factors (90%) with very few influences to accept displaced communities. The study's findings can be used by authorities and policymakers who design and implement post-disaster relocation programmes in understanding a host community's viewpoints and their involvement in making the resettlements successful and sustainable.